DESCRIPTION OF NUTRITIONAL STATUS IN ELEMENTARY SCHOOL STUDENTS: A CASE STUDY OF SD GMIM 65 WINURI, EAST LIKUPANG DISTRICT, NORTH MINAHASA REGENCY - Revolson Alexius Mege; Maria Helena; Sintia Djafar; Megawati Weken; Maiko Polandos; Nonny Manampiring (Indonesian Biodiversity Journal, 2021)
Nutrition plays an important role in the human life cycle from fetus to the elderly. Malnutrition in infants and toddlers can cause growth and development disorders that continue into adulthood if not treated early. Good quality of children can be achieved by ensuring that the process of child development is also good. Growth is quantitative, such as height, weight, and head circumference, and development is the gradual change and improvement of abilities, such as movement, sensory, language, and social abilities. This research was conducted at SD GMIM 65 Winuri. The sample of this study were all elementary school children at SD GMIM 65 Winuri. The results showed that the most common age characteristics of the respondents were 7 years old by 20%, the sex characteristics were mostly male by 52%. Nutritional status based on body mass index (BMI) according to age, respondents have less nutritional status by 18%, normal nutritional status by 50%, overweight status by 14%, nutritional status of obesity I by 8%, and nutritional status of obesity II by 10%.